2009
DOI: 10.1603/029.102.0154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <I>Diuraphis noxia</I> and <I>Rhopalosiphum padi</I> (Hemiptera: Aphididae) on Primary Physiology of Four Near-Isogenic Wheat Lines

Abstract: The impact of feeding injury by the Russian wheat aphid, Diuraphis noxia (Mordvilko) (Hemiptera: Aphididae), and bird cherry-oat aphid, Rhopalosiphum padi (L.) (Hemiptera: Aphididae) on susceptible and resistant wheat, Triticum aestivum L., near-isogenic lines 'Tugela' (susceptible), Tugela-Dn1 (antibiotic), Tugela-Dn2 (tolerant), and Tugela-Dn5 (antixenotic) was evaluated by assessing photosynthetic parameters. Photosynthesis and closely related parameters, pigment composition, and nonstructural carbohydrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Similar to those of Macedo et al (2009), Franzen et al (2007, and Macedo et al (2003), our findings provide further evidence that chlorophyll may not be directly impacted by aphid injury, but rather that the carbon fixation reactions of photosynthesis may be more immediately impacted.…”
Section: Chlorophyll Fluorescence Responsesupporting
confidence: 67%
See 3 more Smart Citations
“…Similar to those of Macedo et al (2009), Franzen et al (2007, and Macedo et al (2003), our findings provide further evidence that chlorophyll may not be directly impacted by aphid injury, but rather that the carbon fixation reactions of photosynthesis may be more immediately impacted.…”
Section: Chlorophyll Fluorescence Responsesupporting
confidence: 67%
“…photosynthetic rates and fluorescence parameters) may help to explain the physiological mechanisms underlying plant resistance. Considerable progress has been made toward identifying the physiological responses of resistant and susceptible wheat to D. noxia (Burd and Elliott 1996;Franzen et al 2007;Haile et al 1999;Heng-Moss et al 2003;Macedo et al 2009), however; only limited information is available on the responses of resistant and susceptible barley to aphid feeding (Burd and Elliott 1996;Miller et al 1994). Research on the physiological responses of resistant and susceptible cereals has focused on several different areas including; chlorophyll and protein content, chlorophyll fluorescence, gas exchange, and molecular pathways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wealth of studies that do not Wt our selection criteria (e.g. Wood et al 1985;Varn and PfeiVer 1989;Meyer and Whitlow 1992;Flynn et al 2006;Macedo et al 2009) have also demonstrated considerable reductions in photosynthetic rates in response to damage by sap-feeders, with only one study (Retuerto et al 2004) showing an opposite eVect. Thus, the data accumulated so far support the conclusion by Welter (1989) and Nabity et al (2009) that sap-feeders and defoliators generally impose opposite impacts on plant photosynthesis.…”
Section: Diverences In Plant Responses To Sap-feeders and Defoliatorsmentioning
confidence: 99%